IMPLEMENTATION OF METRICS ON SOFTWARE DEVELOPMENT IN THE PROVINCIAL ADMINISTRATION SYSTEMS - Abdullah, Adnan (Yayasan Education and Social Center, 2022)
Metrics in software development projects related to the effort and thought required to complete the project and the resources used. The methodology applied, for example, the time needed to complete, experts required, costs incurred, and methods used in software development. This research is an observational study to implement the theory of software metrics in a software development project. The expected result is a guide used to calculate the number of human resources needed in software development, which is calculated in units of person-hours. According to the analysis above, software estimation is used to forecast the resources and costs necessary to complete a software development project the integrity of the new software estimation results. To obtain the most precise estimate, to study and calibrate the estimation formulation constant is necessary to light the current software development project's conditions